Finance and Development, June 2016. (Finance and Development; Finance and Development ;, 2016)
This article profiles iconoclastic economist Dani Rodrik, the Harvard professor whose warnings about the downsides of globalization proved prescient. Rodrik has spent most of his professional life at Ivy League institutions. He has a bachelor's degree from Harvard and master's and PhD degrees from Princeton, followed by a teaching career at Harvard and Columbia. Rodrik's warnings that the benefits of free trade were more apparent to economists than to others were prescient. His skepticism about the benefits of unfettered flows of capital across national boundaries is now conventional wisdom. His successful attack on the so-called Washington Consensus of policies to generate economic growth has made governments and international organizations like the IMF and the World Bank admit that there are many policy recipes that can generate growth. Rodrik's caution about financial globalization is now widely shared, including at the IMF.